Effect Dietary Approaches to Stop Hypertension and Dietary Education in Controlling Blood Pressure among Hypertension Patients - Mayangsari, Mulia; Lutfi, Mohammad (Journal of Bionursing, 2024)
Background: Hypertension or high blood pressure is an increase in systolic blood pressure of more than 140 mmHg and diastolic blood pressure of more than 90 mmHg on two measurements with an interval of five minutes in a state of sufficient rest/quiet. One of the problems that occur is the low effort to control blood pressure in hypertensive patients. Objective: This study aims to analyze the effectiveness of the effect of dietary education on Dietary Approaches to Stop Hypertension (DASH) in controlling blood pressure in hypertensive patients in Blega Village, Blega Health Center Work Area, Bangkalan Regency. Method: The research design used a Quasy Experiment design. The population was 298 adolescent hypertension patients in Blega Village, Blega Health Center Work Area, Bangkalan Regency with 36 samples taken, namely 18 treatments and 19 controls. with sampling technique using probability sampling with purposive sampling technique. The independent variable of this study was education about the DASH diet and the dependent variable was the effort to control blood pressure in hypertensive patients. Data collection techniques using a questionnaire on the subject to be studied. Statistical test using independent t test with (a = 0.05). Results: The results showed that with the results of the independent t test, the p- value was 0.007 <0.05. It was concluded that there was a difference in blood pressure control between the treatment group that was given DASH (Dietary Approaches To Stop Hypertension) education with a booklet and the control group who was given DASH (Dietary Approaches To Stop Hypertension) education and not given a booklet in the working area of the Blega Health Center, Bangkalan Regency Conclusion: Based on the results of these theories, It is recommended for hypertensive patients to increase knowledge about hypertension diet so that they can maintain and regulate a balanced diet to control their blood pressure